Tai-Yuan: Cultural Heritage of Woven Fabrics to Create a Color Scheme for Applied in New Contexts, a Case Study of Khu Bua Sub District, Ratchaburi Province - Utara, Varusa (DEC Journal : Art and Design, 2025)
The objectives of Tai-Yuan: Cultural heritage of woven fabrics to create a color scheme for applied in new contexts, a case study of Khu Bua Sub District, Ratchaburi Province were to explore the cultural heritage of Tai-Yuan woven fabrics of Khu Bua Sub District, Ratchaburi Province, analyze the cultural heritage of Tai-Yuan woven fabrics to discover the identities of the colors in the patterns and the colors in the woven fabric schemes, and create color schemes for applying with creative design and further production of the Tai-Yuan woven fabrics. The qualitative data were collected by questionnaires and interviews. The findings revealed that the patterns and the schemes of Sinh and Tai-Yuan Tin Jok Sinh woven fabrics of Khu Bua Sub District, Mueang District, Ratchaburi Province were produced under the cultural heritage process. However, creativities were still allowed through the use of colors and the shuffles of the patterns. The traditional color scheme was red monochrome inserted with yellow, green, blue and white, with an aggressive contrast of hue. In times past, woven fabrics represented one’s status and were for ritual ceremonies. Nowadays, the contexts of woven fabrics have changed. They have become general and cultural products by applying with constructive economy and the theory of color intensity combined with original colors creating two major color schemes. The color schemes consist of the calming colors and the stimulating colors under the traditional color schemes. The resulting color schemes are adopted to create woven fabric products in the new contexts in order to offer more options and preserve the cultural heritage identities of Tai-Yuan of Khu Bua Sub District, Mueang District, Ratchaburi Province.